Which Psychological Variables Are Associated With Pain and Function Before Surgery for de Quervain’s Tenosynovitis? A Cross-sectional Study - Blackburn, Julia (Clin Orthop Relat Res, 2019)
BACKGROUND: Depression, anxiety, and pain catastrophizing have been associated with worse pain and function in studies of patients with de Quervain’s tenosynovitis. Illness perceptions are the patient’s thoughts and feelings about their illness. More negative perceptions of the illness such as the illness having a long duration or serious consequences are associated with worse physical function in patients with hand osteoarthritis. It is currently unknown whether these psychological factors play a similar role in de Quervain’s. We chose to study patients who have tried nonoperative management and have chosen surgical decompression due to persistent symptoms. Psychological factors may be associated with their ongoing pain and impaired function, so it is particularly important to investigate the role of psychosocial factors that may be targeted with non-invasive interventions. QUESTIONS/PURPOSES: Which psychological variables are independently associated with baseline pain and function in patients undergoing surgical treatment for de Quervain’s tenosynovitis, after controlling for clinical and demographic variables? METHODS: This cross-sectional study included data from a longitudinally maintained database on 229 patients who had surgery for de Quervain’s tenosynovitis between September 2017 and October 2018. All management options were discussed with patients, but many had already tried nonoperative management and chose surgery once referred to our institution. Our database included 958 patients with de Quervain’s, with 69% (659) managed nonoperatively and 34% (326 of 958) who underwent surgical decompression. A total of 70% (229 of 958) completed all questionnaires and could be included in the study. With the numbers available, we found no differences between those included and those not analyzed in terms of age, gender, duration of symptoms, BMI, smoking status, and workload. Patients completed the Patient-Rated Wrist/Hand Evaluation (PRWHE), Patient Health Questionnaire for emotional distress, Pain Catastrophizing Scale (PCS), and the Brief Illness Perception Questionnaire. We investigated the relative contribution of patient demographics and individual psychosocial factors using a hierarchical multivariable linear regression model. In the first step we considered how demographic factors were associated with the baseline PRWHE score. In the second step we investigated the effect of pain catastrophizing and emotional distress on the baseline PRWHE score after accounting for confounding demographic factors. In the final step, the effect of illness perceptions on baseline PRWHE were considered after accounting for the confounding effects of demographic factors as well as pain catastrophizing and emotional distress. RESULTS: After controlling for confounding variables including workload and emotional distress, a more negative patient perception of the consequences of their condition and worse pain catastrophizing were associated with worse pain and function (consequences, β = 0.31; p < 0.01, pain catastrophizing β = 0.17; p = 0.03). A hierarchical multivariable regression analysis found that 11% of variance in baseline pain and function was explained by pain catastrophizing and emotional distress. Illness perceptions brought the total explained variance of the final model to 34%. CONCLUSIONS: More negative perceptions of the consequences of de Quervain’s tenosynovitis and worse pain catastrophizing are associated with worse pain and reduced function at baseline in patients awaiting surgical decompression of de Quervain’s tenosynovitis. In light of these findings, future studies might explore interventions to reduce pain catastrophizing and lower the perceived consequences of the condition. This may reduce the number of patients choosing surgical decompression or may also improve surgical outcomes. Further work should consider if these psychological factors are also associated with postoperative patient-reported outcomes. LEVEL OF EVIDENCE LEVEL: III, therapeutic study.